2016
DOI: 10.1016/j.sjbs.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of diesel fuel hydrocarbons by mangrove fungi from Red Sea Coast of Saudi Arabia

Abstract: Mangrove sediments were collected from major mangrove stands on the Red Sea Coast of Saudi Arabia. Forty five isolates belonging to 12 genera were purified and five isolates as well as their consortium were found to be able to grow in association with petroleum oil as sole carbon source under in vitro conditions. The isolated strains were identified based on internal transcribed spacer (ITS) rDNA sequence analysis. The fungal strains with the greatest potentiality to degrade diesel oil, without developing anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 23 publications
1
46
0
3
Order By: Relevance
“…Different studies have identified numerous fungal genera capable of utilizing crude oil as a source of carbon and energy, including Cephalosporium, Rhizopus, Paecilomyces, Alternaria, Mucor, Talaromyces, Gliocladium, Aspergillus, Fusarium, Rhodotolura, Cladosporium, Geotrichum, Penicillium, Torulopsis and Pleurotus [5][6][7]. The aim of our study was to isolate and identify oil-degrading fungal strains from the coastal area of the Red Sea in Yanbu region contaminated with crude oil, as our previous study showed that this region has potent crude-oil degrading bacterial strains [8].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have identified numerous fungal genera capable of utilizing crude oil as a source of carbon and energy, including Cephalosporium, Rhizopus, Paecilomyces, Alternaria, Mucor, Talaromyces, Gliocladium, Aspergillus, Fusarium, Rhodotolura, Cladosporium, Geotrichum, Penicillium, Torulopsis and Pleurotus [5][6][7]. The aim of our study was to isolate and identify oil-degrading fungal strains from the coastal area of the Red Sea in Yanbu region contaminated with crude oil, as our previous study showed that this region has potent crude-oil degrading bacterial strains [8].…”
Section: Introductionmentioning
confidence: 99%
“…3,13,14 En suelo impactado por este ARA una manera de facilitar la siembra de P. vulgaris y V. sativa es potenciarlo con Micromonospora echinospora y/o Penicillium chrysogenum para minimizar al estrés causado por la fitotoxicidad del ARA, principalmente porque ambos microorganismos oxidan los componentes aromáticos del ARA. 15,16 Con base en lo anterior, el objetivo de este trabajo fue analizar la dinámica de BIS de un suelo impactado por 75000 ppm de ARA, y reducirlo a un valor inferior al máximo permisible por la NOM-138.…”
Section: Introductionunclassified
“…The mean degradation percentage of spent engine oil in different species of fungi after incubation for seven days. (Ghanem, Al-Garni, & Alhomodi, 2015) Able to synthesize various types of enzymes such as lignin peroxidase, lipase, and catalase, which contributed to its capability in tolerating hydrocarbons (Gupta, 2016;Vatsyayan & Goswami, 2016) Able to produce biosurfactants (Adekunle et al, 2015;Kiran et al, 2009) Able to produce ligninolytic enzymes such as lignin peroxidase and manganese peroxidase (Ameen, Moslem, Hadi, & Al-Sabri, 2016) Six species of fungi, which produced significant reduction in spent engine oil content, were identified according to maximum query cover and highest identity percentage with lowest error value through BLAST: Penicillium simplicissimum, Aspergillus nidulans, Aspergillus niger, Trichoderma longibrachiatum, Aspergillus ustus, and Aspergillus flavus. The ability of these fungi to grow in selective media without a carbon source (BHB) confirmed their ability to utilize spent engine oil as a substrate for growth (Thenmozhi et al, 2013).…”
Section: Exhibitmentioning
confidence: 99%